THE INFLUENCE OF THE BRAZILIAN CERRADO DEFORESTATION IN GRAIN CULTURE AND ITS CONSEQUENCES TO LOSSES THE SOIL IN THE CACHOEIRA DOURADA RESERVOIR REGION – CENTRAL - WESTERN BRAZIL - Pereira Cabral, João Batista; Becegato, Valter Antonio; Santos, Francismário Ferreira dos (Geoambiente On-line, 2013)
The erosivity index (EI30) and its spatialization were determined for the contribution basins of the Cachoeira Dourada hydroelectric system reservoir, located between the states of Goiás and Minas Gerais and limited by coordinates 640000-760000 m W and 7910000-7975000 m N. Average monthly and annual rainfall data corresponding to eight localities and to a 30-year period were treated. It was observed that in this period the average annual rainfall was 1441 mm, the highest and lowest indexes having occurred respectively in January and July (7.5 mm). EI30 varied from 7100 to 8500 MJ mm (ha h)-1. The most representative period was October to March, corresponding to 7880.3 MJ mm (ha h)-1and 94% of the average annual EI30. The average rainfall variation coefficient for all stations was 82.73%. There is an irregular rainfall distribution in the region and consequently a non-uniform spatialization of the erosivity indexes within the influence area of the reservoir. The highest rainfall values coincide with the period of soil preparation and development of annual-cycle plants, mainly soybean and corn.